Role of Social Determinants of Health in Reproductive Cancer Care Among Women: A cross-sectional survey from diverse demographic and regional settings in India - Padmaja Gadiraju; C Vanlalhruaii; Ranjit Kumar Dehury; Punam Singh; Imteyaz Ahmad; Parthsarathi Dehury (ACHSM, 2024)
Access to reproductive cancer care in India is significantly affected by social determinants of health. Reproductive cancers, including cervical, ovarian, and uterine cancers, constitute a significant health challenge for women in India. This cross-sectional survey aims to comprehensively assess the landscape of reproductive cancer care among women in India, exploring access, awareness, and barriers to timely diagnosis and treatment. This study highlights challenges in delivering care for reproductive cancers among women in India. A cross-sectional survey design was adopted, involving a representative sample of women from four diverse geographical regions, urban and rural settings, and varying socioeconomic backgrounds. Structured interviews were conducted, and questionnaires were used to collect data on participants' awareness of reproductive cancers, utilization of healthcare facilities, and experiences related to access to cancer care. The study adopted a convenient sampling approach and captured data from 509 women diagnosed with reproductive cancer. The collected data were analysed using the SPSS 25 version. Univariate, bivariate and multivariate analyses were performed. The survey identified one-fourth of the respondents as having ovarian cancer, and 23.4% were diagnosed with cervical cancer. One-third of the study respondents were diagnosed with breast cancer, and 18% had other reproductive system cancers. The survey also assesses the prevalence of risk factors contributing to the incidence of reproductive cancers. Socioeconomic status, education level, rural‒urban settings, and cultural beliefs influence the healthcare-seeking behavior of the study participants. Insufficient knowledge, the stigma of reproductive health problems, and a lack of family income frequently discourage women from obtaining timely medical treatment.